Autologous cord blood cell infusion in preterm neonates safely reduces respiratory support duration and potentially preterm complications. (8th November 2019) - Ren, Zhuxiao; Xu, Fang; Zhang, Xiaoling; Zhang, Chunyi; Miao, Jiayu; Xia, Xin; Kang, Mengmeng; Wei, Wei; Ma, Tianbao; Zhang, Qi; Lu, Lijuan; Wen, Jiying; et al.
Abstract: Preterm birth and its complications are the leading cause of neonatal death. The main underlying pathological mechanisms for preterm complications are disruption of the normal maturation processes within the target tissues, interrupted by premature birth. Cord blood, as a new and convenient source of stem cells, may provide new, promising options for preventing preterm complications. This prospective, nonrandomized placebo controlled study aimed at investigating the effect of autologous cord blood mononuclear cells (ACBMNC) for preventing preterm associated complications. Preterm infants less than 35 weeks gestational age were assigned to receive ACBMNC (5 × 10 7 cells/kg) intravenous or normal saline within 8 hours after birth. Preterm complication rates were compared between two groups to demonstrate the effect of ACBMNC infusion in reducing preterm complications. Fifteen preterm infants received ACBMNC infusion, and 16 infants were assigned to the control group. There were no significant differences when comparing mortality and preterm complication rates before discharge. However, ACBMNC infusion demonstrated significant decreases in duration of mechanical ventilation (3.2 days vs 6.41 days, P = .028) and oxygen therapy (5.33 days vs 11.31 days, P = .047). ACBMNC infusion was effective in reducing respiratory support duration in very preterm infants. Due to the limited number of patients enrolled, powered randomized controlled trials are needed to better define its efficacy. : Abbreviations: ACBMNC autologous cord blood mononuclear cells BPD bronchopulmonary dysplasia CP cerebral palsy GA gestational age HIE hypoxic ischemic encephalopathy IV intravenous IVH intraventricular hemorrhage LOS late onset sepsis MSC mesenchymal stem cells NEC necrotizing enterocolitis PS pulmonary surfactant RBC red blood cells RDS respiratory distress syndrome ROP retinopathy of prematurity SPC stem and progenitor cells UCB umbilical cord blood VAP ventilation-associated pneumonia Abstract : Autologous cord blood cells infusion in preterm neonates safely reduces respiratory support duration and potentially preterm complications.